Limbo: the unintended consequences of home buyout programmes on peripheral communities. (19th October 2020) - Binder, Sherri B.; Ritchie, Liesel A.; Bender, Rose; Thiel, Alexis; Baker, Charlene K.; Badillo, Emily; Goodfellow, Sophia; Kulp, Bethann; Weir, Paige
Abstract: Home buyout programmes are designed to permanently relocate households away from areas that are vulnerable to future hazards, though their impacts are not well understood. Among the least understood impacts of these programmes are those related to non-participating households located near buyout zones. Here, we present findings from a study of Oakwood, NY, a peripheral community that was impacted by a buyout programme in a neighbouring community. Drawing on qualitative data collected three-and-a-half years after Hurricane Sandy, we examine the experiences of affected households through the lens of Conservation of Resources theory. We find that residents of the peripheral community experienced a suite of losses associated with the implementation of the buyout, including losses in the physical environment that impacted their sense of safety, losses in conditions resources reflecting a perception that the government had failed to act in their best interests, and the threat of long-term financial losses associated with post-buyout land use decisions over which they had no control. Taken together, these losses contributed to an experience of stalled recovery that left residents in a permanent state of limbo . Policy implications related to the consideration of peripheral communities in the assessment and implementation of buyouts are discussed.